The Relationship Between Personality Traits and General Health of Nursing Students - Mahnaz Seyedoshohadaee; Muhammad Hossain Hakimi; Marjan Mardani; Hameed Baqaee (Iran University of Medical Sciences, 2017)
Background: Students' general health is of great importance and serious attention should be paid to their health-related issues. Some personal characteristics such as their traits may be the most influential factors in their general health. Thus, the current study was conducted to determine the relationship between personal traits and general health in nursing students. Methods: This is a descriptive correlational research which was conducted on 194 undergraduate nursing students of Qom Medical University, Qom, Iran, in 2015. Samples were chosen by census method. The relevant data were collected by demographic information, the shortened form of five personality traits assessment, and general health questionnaires. The data were analyzed using Pearson correlation and t-tests by SPSS V. 23.  Results: A significant positive correlation was found between personality traits of extraversion, agreeableness, conscientiousness and general health, while there was a significant negative correlation between neuroticism and general health. Also with regard to general health domains, the maximum mean (SD) belonged to social dysfunction with 8.72 (3.420), and the minimum to depression with 3.27 (4.368). Study results indicated that maximum score belonged to conscientiousness and minimum to neuroticism among the personality traits. Conclusion: Since personality traits play an influential role in different aspects of students' general health, it is expected that factors affecting nursing students' general health be paid more attention and appropriate training for raising health services for students be planned and provided.